2020
DOI: 10.1108/srj-02-2019-0084
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing CSR by Islamic banks: does Jaiz Bank Nigeria, Plc adopt the practice of Islami Bank Bangladesh Limited?

Abstract: Purpose This paper aims to establish whether Jaiz Bank Nigeria, Plc (JBNP) adopts the corporate social responsibility (CSR) practice and disclosure of Islami Bank Bangladesh (IBBL) as the latter provided managerial and technical assistance to the former. Design/methodology/approach The data were extracted from the annual reports and accounts of the banks from 2013 to 2017. Findings The study established that over the period, IBBL had clearly disclosed sector-wise CSR expenditures and the number of benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 19 publications
0
32
0
3
Order By: Relevance
“…First, it is the most populated nation in Africa with about 200 million people dominated by Muslims. Second, the Islamic finance industry in the country is continuously expanding, as one more Islamic bank called Taj Bank Limited emerged lately in 2019 (Umar and Musa, 2020). Third, Nigeria is a member of many prime movers of Islamic finance in the world such as the Islamic Development Bank (IsDB), the Islamic Financial Service Board (IFSB) and the International Islamic Liquidity Management Corporation (IILM).…”
Section: Introductionmentioning
confidence: 99%
“…First, it is the most populated nation in Africa with about 200 million people dominated by Muslims. Second, the Islamic finance industry in the country is continuously expanding, as one more Islamic bank called Taj Bank Limited emerged lately in 2019 (Umar and Musa, 2020). Third, Nigeria is a member of many prime movers of Islamic finance in the world such as the Islamic Development Bank (IsDB), the Islamic Financial Service Board (IFSB) and the International Islamic Liquidity Management Corporation (IILM).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also include four control variables: TYPE denotes if the IFF is a fully Islamic firm or an Islamic window. Umar and Musa (2020) compared CSR adoption between a non-Islamic Nigerian bank and a Bangladeshi Islamic bank. They showed that the non-Islamic Nigerian bank did not adopt CSR disclosure despite receiving significant technical assistance from Bangladesh’s Islamic bank.…”
Section: Methodsmentioning
confidence: 99%
“…The previous study of Ali and Rahman (2015) and Umar and Musa (2020) on Islamic banks in Bangladesh revealed that CSR activities give emphasized on the contribution to community development, social enhancement, education, health, culture and environment. The study of Rana et al (2012), Ali and Rahman (2015), and Ahmed (2013) on conventional banks in Bangladesh identified that CSR activities give emphasized the contribution for improving social relations, environmental benefits, education, health, community development, art, sports and culture.…”
Section: Dimensions Of Corporate Social Responsibility Activities By ...mentioning
confidence: 99%
“…Ali and Rahman (2015) highlighted the CSR activities of Islamic Banks in Bangladesh are health, education, relief, disaster, environment, social welfare, culture and sports. Another study by Umar and Musa (2020) showed that Islamic banks in Bangladesh are giving benefits through their CSR activities in community development, disaster relief, education, environment and health. From the earlier discussion, it is immense to measure the CSR performances based on social, economic and environmental responsibilities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation